Datafikasi Melalui Fashion Modeling Di Universitas X Malaysia - Beng, Jap Tji; Nurkholiza, Rahmiyana; Tiatri, Sri; Hai, Sam Toong; Dinatha, Vienchenzia Oeyta D.; Margareta, Margareta; Salsabila, Tasya Mulia; Sefira, Fasia Meta; Zahro, Tiara (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2025)
Digital transformation has precipitated a substantial evolution to the fashion modelling sector. Term of digital transformation through big data, driven by the urgency to teach data literacy to students. This marked and dominated by the concept of datafication, which is the transformation of intangible elements into quantifiable data. This study examines students understanding of datafication level through fashion modeling. The study employs a quantitative method with a pre-test and post-test design consisting of 10 questions. The research variables are the intervention of datafication learning in fashion modelling and changes in students understanding levels. The study participants include 31 students from university X in Malaysia. The results of paired samples t-test analysis showed a significant increase, with an average score difference of 2.45 (p= 0.017). Additionally, the decrease in standard deviation and standard error of the mean values indicated stability in understanding after the intervention. The findings of this study contribute to data-based learning strategies and strengthen the connection between conceptual understanding and practical application.Keyword: Datafication; Digital Transformation; Fashion; Modeling; Big Data   Abstrak Transformasi digital telah membawa perubahan signifikan di sektor fashion modeling. Perkembangan transformasi digital melalui big data didukung oleh urgensi memperkenalkan pembelajaran data kepada mahasiswa menjadi penting. Perkembangan ini ditandai dan di dominasi oleh konsep datafikasi, yang merupakan transformasi elemen tidak berwujud menjadi sebuah data terkuantifikasi. Penelitian ini bertujuan untuk menganalisis dan mengevaluasi tingkat pemahaman datafikasi melalui fashion modeling. Penelitian ini menggunakan metode kuantitatif dengan desain pre-test dan post-test sebanyak 10 butir pertanyaan. Variabel penelitian ini adalah intervensi pembelajaran datafikasi fashion modeling dan perubahan tingkat pemahaman mahasiswa. Partisipan penelitian melibatkan 31 mahasiswa di universitas X Malaysia. Hasil analisis paired samples t-test menunjukkan peningkatan signifikan, dengan selisih skor rata-rata sebesar 2.45 (p= 0.017). Selain itu penurunan nilai standar deviasi dan standard error mean menunjukkan indikasi stabilitas pemahaman setelah intervensi. Hasil penelitian ini memberikan kontribusi terhadap strategi pembelajaran berbasis data serta memperkuat keterkaitan antara pemahaman konseptual dan pemaparan praktik.